Comparison of conventional laparoscopic hysterectomy and vNOTES hysterectomy in previous pelvic surgery: a retrospective study - Haliscelik, Mesut Ali; Oglak, Suleyman Cemil; Bagli, Ihsan; Akgol, Sedat; Can, Behzat; Arkan, Kevser; Sanli, Cengiz (Nature Portfolio, 2025)
This study compared the surgical outcomes of total laparoscopic hysterectomy (TLH) and vaginal-assisted natural orifice transluminal endoscopic surgery (vNOTES) in patients with a history of gynecologic and obstetric surgery. This cross-sectional study included 100 women who underwent TLH (n = 50) and vNOTES hysterectomy (n = 50) for benign gynecological pathologies. The demographic features and surgical outcomes of all the patients were recorded retrospectively. Postoperative hematocrit values, Visual Analog Scale (VAS) scores (6-24th hour), uterine weights, operation time, hospital stay, postoperative analgesic application requirement, blood transfusion, vaginal cuff closure time, and intraoperative and postoperative complications were assessed. There were no differences in demographic features between the groups. The need for analgesic application was similar between groups (p = 0.590). Vaginal closure time was significantly shorter in the vNOTES group (p < 0.001). The surgery time and hospital stay were significantly shorter in the vNOTES group (p = 0.001 and p = 0.006, respectively), and there was no difference in complication rates between the groups (p = 0.992). The preoperative Htc values were similar in both groups (P = 0.980). There was no significant difference in the postoperative Htc values (p = 0.901). Postoperative 6th hour VAS score of the vNOTES group was significantly lower than that of the TLH group (p = 0.001). The vNOTES hysterectomy procedure has more advantages than TLH in terms of minimally invasive surgery, even in patients with a history of gynecologic and obstetric surgery.
Keywords: Hysterectomy; Laparoscopy; Natural orifice transluminal endoscopic surgery